2023
DOI: 10.3390/ma16031222
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Nanoparticulate Y2O3 Modified AlSi10Mg Alloys Manufactured by Selective Laser Melting

Abstract: AlSi10Mg has a good forming ability and has been widely accepted as an optimal material for selective laser melting (SLM). However, the strength and elongation of unmodified AlSi10Mg are insufficient, which limits its application in the space industry. In this paper, yttrium oxide (Y2O3) nanoparticles modified AlSi10Mg composites that were manufactured using SLM. The effects of Y2O3 nanoparticles (0~2 wt.% addition) on the microstructure and mechanical properties of AlSi10Mg alloys were investigated. An ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…This strategy effectively mitigates the aforementioned shortcomings associated with monolithic aluminum alloys. Extensive research has been conducted to explore the impacts of diverse reinforced particles, such as oxides [55][56][57], carbides [58][59][60][61], nitrides [62][63][64], borides [65][66][67], and various allotropes of carbon [68][69][70], on the microstructure and mechanical properties of AlSi10Mg composites fabricated through an L-PBF approach. The findings from these studies have demonstrated promising outcomes, indicating significant enhancements in the resulting composites' microstructural characteristics and mechanical properties.…”
Section: Enhancing Performance Through Composite Reinforcementsmentioning
confidence: 99%
“…This strategy effectively mitigates the aforementioned shortcomings associated with monolithic aluminum alloys. Extensive research has been conducted to explore the impacts of diverse reinforced particles, such as oxides [55][56][57], carbides [58][59][60][61], nitrides [62][63][64], borides [65][66][67], and various allotropes of carbon [68][69][70], on the microstructure and mechanical properties of AlSi10Mg composites fabricated through an L-PBF approach. The findings from these studies have demonstrated promising outcomes, indicating significant enhancements in the resulting composites' microstructural characteristics and mechanical properties.…”
Section: Enhancing Performance Through Composite Reinforcementsmentioning
confidence: 99%